Evaluation of Host Immune Response in Diabetic Foot Infection Tissues Using an RNA Sequencing-Based Approach - Heravi, Fatemah Sadeghpour; Zakrzewski, Martha; Aboulkheyr Estarabadi, Hamidreza; Vickery, Karen; Hu, Honghua (Frontiers in Microbiology, 2021)
The normal continuity and cohesion of skin tissue can be affected by invading pathogens and lead to a series of complicated physiological events and expression of various inflammatory cytokines. We have investigated host transcriptomic profiles using an RNA-based sequencing approach in diabetic foot infections (DFIs) with different disease severity. The hierarchical clustering of the top 2000 genes showed the expression of four main clusters (A, B, C, and D). Clusters A and D were enriched in genes mainly involved in the recruitment of inflammatory cells and immune responses and clusters B and C were enriched in genes related to skin cells development and wound healing processes such as extracellular structure organization and blood vessel development. Differentially expression analysis showed more than 500 differentially expressed genes (DEGs) between samples with a low number of bacterial virulence factors (control) and samples with a high number of bacterial virulence factors (perturbation). Up-regulated and down-regulated genes were mainly involved in innate and adaptive immune systems and transport of mature mRNAs, respectively. Our results demonstrated the importance of inflammatory cytokines in adaptative and native immunity in the progression of DFIs and provided a useful groundwork of DFIs gene expression profiles. Identified pathways in this study particularly immune chemokines, Rho GTPases, and corresponding effectors might be important therapeutic targets through modulation of cytoskeletal function and manipulation of cytokines in the improvement of DFIs.